Increasing the use of biological pesticides in integrated pest management programs - Marrone, Pamela G. (Frontiers in Insect Science, 2025)
While biopesticides have been around for 70 years, starting with Bacillus thuringiensis bioinsecticides, they are experiencing rapid growth as the products have gotten better and more science-based and there are more restrictions on synthetic chemical pesticides. The growth of biopesticides is projected to continue to outpace that of chemical pesticides, with compounded annual growth rates of 10%–20% versus single digits for chemicals. When integrated into pest management programs, biopesticides offer the potential for higher crop yields and quality than chemical-only programs. Added benefits include the reduction or elimination of chemical residues, therefore easing export, delay in the development of resistance by pests and pathogens to chemicals, shorter field re-entry, biodegradability and lower carbon footprint and greenhouse gas emissions, and low risk to non-target organisms, including pollinators. However, many challenges still exist to drive further the adoption of biopesticides. These include lack of awareness and education in how to test and deploy their unique modes of action in integrated programs, resulting in lingering perceptions about performance and cost-effectiveness. This article addresses these issues with suggestions on how to increase farmer and key influencer confidence in the deployment of biologicals in integrated pest management (IPM) programs, including adjusting IPM thresholds and practice based on the modes of action of biopesticides compared to synthetic chemicals.